On Sequentially Defined Function Spaces and Bounded Linear Functionals - Supama (Journal of Research in Mathematics Trends and Technology, 2021)
In this paper, we construct a sequentially defined function space $L_{p,q}(Ω)$ and observe its topological properties. Further, we formulate necessary and sufficient conditions for bounded linear functionals on the space.